2019
DOI: 10.1370/afm.2438
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of a Smartphone-Operated, Single-Lead Electrocardiography Device for Detection of Rhythm and Conduction Abnormalities in Primary Care

Abstract: PURPOSE To validate a smartphone-operated, single-lead electrocardiography (1L-ECG) device (AliveCor KardiaMobile) with an integrated algorithm for atrial fibrillation (AF) against 12-lead ECG (12L-ECG) in a primary care population. METHODS We recruited consecutive patients who underwent 12L-ECG for any nonacute indication. Patients held a smartphone with connected 1L-ECG while local personnel simultaneously performed 12L-ECG. All 1L-ECG recordings were assessed by blinded cardiologists as well as by the smart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 28 publications
2
43
5
1
Order By: Relevance
“…A study concluded that the device managed to distinguish between atrial fibrillation and a normal heart rhythm with a sensitivity of 93, and a specificity of 94%, respectively. Its sensitivity increased to 99% when a medical professional reviewed the reading 26 .…”
Section: Questionsmentioning
confidence: 99%
“…A study concluded that the device managed to distinguish between atrial fibrillation and a normal heart rhythm with a sensitivity of 93, and a specificity of 94%, respectively. Its sensitivity increased to 99% when a medical professional reviewed the reading 26 .…”
Section: Questionsmentioning
confidence: 99%
“…There is mounting evidence for the utility of integrating singlelead ECGs into healthcare provision in a number of settings. [10][11][12][13][14][15][16] This pilot initiative aimed to test the feasibility of integrating a single-lead hand-held ECG system, the AliveCor, into community monitoring of treatment in patients with recently diagnosed fast AF and opportunistic community diagnosis of AF.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Egy tanulmány megállapította, hogy a KardiaBand 93 százalékos érzékenységgel és 94 százalékos specificitással képes megkülönböztetni a pitvarfibrillációt és a normális szívritmust. Az érzékenység 99 százalékosra nőtt, amikor orvos is értékelte az adatokat (Himmelreich et al, 2019).…”
Section: Hogyan Lehet Az Ai Technológia a Mindennapi Orvoslás Része?unclassified